EVALUASI EFEKTIFITAS KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH (BOS) DI LEMBAGA MTS YPPA CIPULUS - Muhammad fauzan; Jia Nurfajriyani Imsaqi; Moh. Sugandi (lembaga Sepercenter, 2026)
School Operational Assistance (BOS) funds are one of the government programs aimed at supporting educational operational financing and improving the quality of educational services in schools. In its implementation, BOS fund management is required to be carried out effectively, transparently, accountably, and in accordance with the technical guidelines established by the government. However, in practice, there are still various obstacles that affect the effectiveness of BOS fund management, both in terms of administration, reporting, and coordination among the parties involved. This study aims to evaluate the effectiveness of School Operational Assistance (BOS) fund management at MTs YPPA. This study employed a qualitative approach with a descriptive research design. Data collection techniques were carried out through observation, in-depth interviews, and documentation involving the BOS treasurer, teachers, and related parties involved in BOS fund management. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that administratively, BOS fund management has been implemented in accordance with government technical guidelines. However, its implementation still faces various obstacles, particularly in terms of delays in fund disbursement, technical constraints in digital-based reporting, lack of program evaluation, low stakeholder participation in school budget preparation, suboptimal transparency, and weak coordination among related parties. In addition, the limited competence of human resources also affects the effectiveness of BOS fund management, resulting in the program not being implemented optimally in supporting the improvement of education quality.